The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1558/cj.31594
|View full text |Cite
|
Sign up to set email alerts
|

Looking for a Needle in a Haystack: CALL and Advanced Language Proficiency

Abstract: The goal of this meta-analysis is to evaluate how instructional technology has impacted advanced second language (AL2) development. Although numerous meta-analyses have been conducted within the CALL literature over the past two decades, they primarily focus upon learning outcomes and related effect sizes. None focus on advanced learning per se. Where AL2 is even mentioned, which is only rarely, little or no attention is paid to critical research parameters within the studies that are analyzed. Most notably, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(154 reference statements)
1
2
0
Order By: Relevance
“…Proficiency. In keeping with the results of Burston and Arispe (2018), our findings indicate that almost 60% of the studies do not report the proficiency levelor, if they do, use vague terms that complicate categorization. With limited information, we adopted the general descriptors the authors themselves use (e.g.…”
Section: Research Participantssupporting
confidence: 84%
“…Proficiency. In keeping with the results of Burston and Arispe (2018), our findings indicate that almost 60% of the studies do not report the proficiency levelor, if they do, use vague terms that complicate categorization. With limited information, we adopted the general descriptors the authors themselves use (e.g.…”
Section: Research Participantssupporting
confidence: 84%
“…Even though studies have shown that most L2s would not achieve the Superior level by the time they finish their bachelor's degrees (Malone et al, 2005), research is needed to investigate what happens to students who start their career at an advanced level of proficiency, as is the case for most ESAs and NSs as well as for many SHLLs. Furthermore, until recently, research has focused primarily on Novice and Intermediate levels; few empirical studies have investigated Advanced levels (Burston & Arispe, 2018; Montrul, 2013; Swender et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research reported shows that the majority of CALL teaching is aimed at beginners and intermediate students, and focuses on the key language skills. Advanced skills and more complex topics are less frequently addressed (see, e.g., Burston & Arispe, 2018). Yet the latter remain important in the wider language teaching world.…”
Section: The Concentration Of Research Studiesmentioning
confidence: 99%